The simple two-step polydimethylsiloxane transferring process for high aspect ratio microstructures *Project supported by the Natural Science Foundation of Shenzhen (No. JCYJ20160429153110908) and the Science and Technology Development Program of Shaanxi Province (No. 2016GY-091). (August 2018) - Wang, Shaoxi; Feng, Dan; Hu, Chenxia; Rezai, P.
Abstract: High aspect ratio units are necessary parts of complex microstructures in microfluidic devices. Some methods that are available to achieve a high aspect ratio require expensive materials or complex chemical processes; for other methods it is difficult to reach simple high aspect ratio structures, which need supporting structures. The paper presents a simple and cheap two-step Polydimethylsioxane (PDMS) transferring process to get high aspect ratio single pillars, which only requires covering the PDMS mold with a Brij@52 surface solution after getting a relative PDMS mold based on an SU8 mold. The experimental results demonstrate the method efficiency and effectiveness.